Stressful life events and other associated factors in patients with bipolar disorder current episode depression – A cross-sectional study (Kerala Journal of Psychiatry, 2023)
Background: Bipolar disorder (BD) is a mental illness which leads to considerable difficulties and challenges. The neurobiology of BD has complex underpinnings of gene–environment interactions. One such environmental factor, stressful life events (SLEs) can have adverse impacts on the course and prognosis of BD, however, this is underexplored. Aims and objectives: 1) To estimate the frequency and severity of SLEs in patients with BD-current episode depression 2) To determine the association of severity of depression with SLE, sociodemographic and illness-related factors. Methods: This was a cross-sectional study done on 100 consecutive patients diagnosed to have BD-current episode of depression (ICD-10), attending Psychiatry department at Pushpagiri Medical College, Thiruvalla, Kerala. A semi-structured proforma, Hamilton Rating Scale for Depression, Presumptive Stressful Life Events Scale and Brief Psychiatric Rating Scale were used. Results: About 73% of patients reported SLEs – of which 65% had mild/moderate and 8% had severe stress. A statistically significant association was found between SLEs and ‘very severe’ depressive episode.  Past suicide attempt, the first episode as depression and lesser duration of the last episode also showed a statistically significant association with severity of depression. Conclusion: As the stressful life experiences have been linked to 'very severe' depressive episodes in a major way, understanding the association of stressful life events and BD can help in predicting further relapses and complications like suicide. It can aid in both symptom reduction and improving quality of life as well.
Keywords: Stressful life events; bipolar disorder; depression